Konvergensi Pendidikan Lingkungan dan Spiritualitas: Analisis Tematik atas Program Sekolah Adiwiyata dan Filsafat Ekologi Seyyed Hossein Nasr - Muhammad Alamsyah Putra; Nataliya Pratiwi (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
The global ecological crisis reflects not only environmental degradation but also a spiritual crisis that disrupts the sacred relationship between humans and nature. This study explores the convergence between Indonesia’s Adiwiyata School Program and Seyyed Hossein Nasr’s philosophy of Islamic eco-spirituality, aiming to reveal how environmental education can be integrated with spiritual values. Employing a qualitative Systematic Literature Review (SLR) and thematic analysis, this research systematically identifies and synthesizes findings from previous studies on both Adiwiyata and Nasr’s ecological thought. The results indicate that the Adiwiyata program contributes significantly to shaping students environmental and moral awareness through behavioral habituation, curriculum integration, and school culture development. However, its philosophical and spiritual depth remains limited compared to Nasr’s critical perspective on modernity, desanctification of nature, and the unity of science and spirituality. The synthesis proposes an integrative conceptual framework that aligns technical environmental education with spiritual transformation, forming an eco-spiritual paradigm in schooling. The study concludes that embedding Nasr’s eco-spiritual philosophy into Adiwiyata can transform it from a behavioral-based environmental program into a transformatory model of sacred ecological education. Future research is recommended to empirically test this conceptual model and to explore comparisons with other eco-spiritual thinkers.